AEA Randomized Controlled Trials 2020
DOI: 10.1257/rct.5733
|View full text |Cite
|
Sign up to set email alerts
|

Love in the Time of HIV: Testing as a Signal of Risk

Abstract: The HIV epidemic in southern Africa has important consequences for economic development. The epidemic could be stopped by a universal test and treat policy, as antiretroviral drugs block the spread of the virus. However, demand for HIV testing and treatment are surprisingly low. This paper develops a model in which the decision to seek an HIV test is a signal of infection, and those who seek a test are subject to statistical discrimination from potential sexual partners. We evaluate an information experiment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We are not aware of other studies that have described PLWH's perspectives on Treat All policies, and thus our findings provide an important and reassuring contribution to the field. Our findings also add to the emerging literature suggesting that emphasizing the social benefits of Treat All, including decreasing the risk of HIV acquisition in the population and the contribution to the overall health of society could successfully address some of the barriers to care for PLWH [43].…”
Section: Plos Onesupporting
confidence: 54%
“…We are not aware of other studies that have described PLWH's perspectives on Treat All policies, and thus our findings provide an important and reassuring contribution to the field. Our findings also add to the emerging literature suggesting that emphasizing the social benefits of Treat All, including decreasing the risk of HIV acquisition in the population and the contribution to the overall health of society could successfully address some of the barriers to care for PLWH [43].…”
Section: Plos Onesupporting
confidence: 54%
“…To assess this pathway, Derksen et al [87] conducted a large cluster-randomized trial of a community-level TasP education intervention in rural Malawi. A single community meeting was conducted in 122 villages.…”
Section: Impact Of Disseminating Information On Tasp/u = Umentioning
confidence: 99%
“…Fifth, most existing studies of impact delivered TasP/U = U messaging alongside other interventions such as enhanced adherence counseling [85,86] or enhanced messaging around other benefits of modern single-pill, low-toxicity ARVs [45]. Just one study enabled inferences on the impact of TasP/U = U messaging alone [87]. These multimodal interventions correctly diagnose that knowledge and attitudes regarding TasP are precursors and foundations of behavioral intent, but are not sufficient to cause behavior change.…”
Section: Our Review Had Several Limitationsmentioning
confidence: 99%
“…[11][12][13] This potential is further supported by prior randomized controlled trials that have demonstrated that behavioral interventions designed in part to improve understanding of treatment as prevention among PLWH can improve ART adherence, viral suppression, and intentions to rely on treatment as prevention. 36,37,40 There were survey questions within some domains that did not improve after exposure to B-OK -in particular, hypothetical scenarios asking participants to estimate the likelihood of sexual transmission from an undetectable partner and the likelihood of harm from HIV for a person with an undetectable viral load, intentions to stay on HIV treatment, and perceived understanding of illness. Participants had very high baseline scores for these questions, so it is unsurprising that there were no significant changes seen after the intervention.…”
Section: Discussionmentioning
confidence: 99%